2020
DOI: 10.1007/s10764-019-00119-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group Size and Individual Characteristics on Intergroup Encounters in Primates

Abstract: Intergroup encounters are common in nonhuman primates and can vary from affiliative to aggressive. We extracted data from the literature to test five different hypotheses: 1) where there are group size differences between opposing groups, whether the larger group is more likely to win an intergroup encounter than the smaller group; 2) whether the likelihood of a group engaging in aggressive intergroup encounters increases with group size; and 3-5) whether dominant, older individuals, and/or males are more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 61 publications
2
39
1
Order By: Relevance
“…Thus, collective group defense may present a collective action problem (Langergraber et al 2017;Willems et al 2013Willems et al , 2015, especially with increasing group size and in species that live in a social system with high fission-fusion dynamics in which group members do not permanently associate. However, in many species, including humans, collective action and strength in numbers are key during intergroup conflicts (Majolo et al 2019;Willems et al 2015;Wrangham 1999), suggesting that species may overcome the collective action problem. Indeed, in humans, intergroup competition is known to engender solidarity, affiliation, and cohesion within a group (Bernhard et al 2006;Gneezy and Fessler 2012;Puurtinen and Mappes 2009;Yamagishi and Mifune 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, collective group defense may present a collective action problem (Langergraber et al 2017;Willems et al 2013Willems et al , 2015, especially with increasing group size and in species that live in a social system with high fission-fusion dynamics in which group members do not permanently associate. However, in many species, including humans, collective action and strength in numbers are key during intergroup conflicts (Majolo et al 2019;Willems et al 2015;Wrangham 1999), suggesting that species may overcome the collective action problem. Indeed, in humans, intergroup competition is known to engender solidarity, affiliation, and cohesion within a group (Bernhard et al 2006;Gneezy and Fessler 2012;Puurtinen and Mappes 2009;Yamagishi and Mifune 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The best-supported single RHP proxy in intergroup contests is group size: the number of members in each group. A recent meta-analysis affirmed this in primates [12], and group size is relevant in other taxa from ants (e.g., wood ants Formica rufa) [24], to lions (Panthera leo) [25], to birds (green woodhoopoes Phoeniculus purpureus) ( [26]; cf [27] where group size does not predict outcomes in greater anis Crotophaga major). However, proxies other than absolute numbers might be important.…”
Section: Open Accessmentioning
confidence: 98%
“…In the context of intragroup conflict, observations of both chimpanzees and bonobos also suggest females tend to recruit coalition partners primarily to defend kin and friends against male aggression, whereas males tend to build coalitions primarily to compete for high rank and the mating opportunity it affords (Newton-Fisher, 2006;Tokuyama and Furuichi, 2016). However, a recent metanalysis of relevant primate studies revealed only weak support for the effect of sex on the frequency of aggression displayed toward outgroup individuals during intergroup encounters (Majolo et al, 2020). Moreover, the meta-analysis found significant variation in female participation in intergroup aggression across and within species (Majolo et al, 2020).…”
Section: Ecological Functions Of Sex Differences In Leadership Sexual Selection and Sex-specific Leadershipmentioning
confidence: 99%